Sport tourism development - Kalacas, Maria Rellie B. (Burlington, Canada Society Publishing, 2022)
"Tourism is an important sector for economic development in a country. With a year ahead full of important sporting events, we look at how sports tourism has grown in importance from niche market to multi-billion dollar business. Sport and tourism each contribute a great deal to the global economy and have become an element in the armoury of politicians, planners and economists seeking to regenerate local economies. The trend to increase sport touristic experiences and to provide them in faraway, often very different cultures simply increases the importance of addressing both the potential positive and the negative sociocultural impacts of sport tourism. This book critically explores sport-related tourism drawing on the fields of sport management, sports marketing, economic, sports geography, and tourism studies." --
Fundamentals of sport tourism -- Sport tourism destination: changes, trends, and management -- Destination marketing and sport events management -- Sport event impacts -- Sport tourism and rural development -- Sport tourism and urban regeneration -- Sustainability and sport tourism development -- Current and future perspective of sport tourism
Keywords: Sports tourism; Sports tourism -- Economic aspects